2000
DOI: 10.2224/sbp.2000.28.4.343
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Effects of Linguistic Abilities on Communication Stress, Measured by Blinking and Heart Rate, During a Telephone Situation

Abstract: In the present study we examined the differences in communication stress responses, as they were affected by levels of linguistic ability, and measured by heart rate and blinking during a telephone communication. Nine female participants were selected as representative of the medium level of communication skills and linguistic level assessed by questionnaires. They were assigned to 3 conversation tasks: Japanese, English, and French. The questionnaires (STAI and Iceberg Profile) were also assessed. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…A tantalizing possibility for why blinks result in higher-order cognitive processing is that we have learned associations between blink rate and level of interest, arousal level, stress and/or other factors integral to social interactions. These cognitive and affective states can in turn affect dopaminergic systems which have a direct relationship with blink rate (Brozoski et al, 1979 ; Karson, 1983 ; Coull et al, 1995 ; Coull, 1998 ; Hirokawa et al, 2000 ; Dreisbach et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…A tantalizing possibility for why blinks result in higher-order cognitive processing is that we have learned associations between blink rate and level of interest, arousal level, stress and/or other factors integral to social interactions. These cognitive and affective states can in turn affect dopaminergic systems which have a direct relationship with blink rate (Brozoski et al, 1979 ; Karson, 1983 ; Coull et al, 1995 ; Coull, 1998 ; Hirokawa et al, 2000 ; Dreisbach et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Especially in social situations such as a group discussion and a conversation among more than two persons, as in this experiment, the blink rate allows an experimenter to analyze one aspect of the mental state by counting it utilizing the video record. Hirokawa, Yagi, and Miyata (2000) also assessed blink rate during conversation situations, and suggested that the blink rate could be an index of physiological state. Regarding the relationship between stress and blink rate, the authors expected that when an individual felt anxiety or tension, his/her blink rate would increase.…”
mentioning
confidence: 99%
“…Leal & Vrij represented blinks in increased cognitive demand during lying [ 8 ]. Ponder and Kennedy reported about blinks during emotional excitement [ 9 ] and Hirokawa depicted more frequent blinks in highest nervousness [ 10 ]. Cognitive processes have a substantial impact on blink rates, mentally taxing activities like memorization or mathematical computation being associated with an increase in blink rate and inattentiveness (daydreaming) and stimulus tracking being associated with low blink rates.…”
Section: Introductionmentioning
confidence: 99%